Genetic structure and historical demography of inland wetland fish using the endangered Lisbon arched-mouth nase as a case-study - Giulia Riccioni; Manuel Curto; Carlos D. Santos; Maria Judite Alves; Hugo F. Gante; Filipe Ribeiro; Ana Veríssimo (Scientific Reports)
Abstract Inland wetlands are highly diverse, productive ecosystems at the transition between terrestrial and aquatic environments, providing major services to society. They are also under high human pressure and have suffered a progressive decline in total area globally. Here, we describe the genetic diversity and demography of the endangered Lisbon arched-mouth nase Iberochondrostoma olisiponense occurring in the inland wetlands of a major river in southwestern Europe, within a context of extreme habitat changes. Our results highlight the presence of well-structured small population nuclei with evidence of sporadic gene flow at historical and contemporary time scales. Historical reconstructions suggest population isolation consistent with periods of unsuitable habitat conditions severing population connectivity, while small population sizes may be due to limited available habitat coupled to historical as well as recent restricted connectivity among river tributaries. Habitat contraction or loss due to decreased rainfall associated with climate change is expected to impact inland wetland fish regionally, raising additional conservation concerns on species with low genetic diversity and small effective population sizes as I. olisiponense. This study may serve as a proxy for taxa occurring in similar inland wetland ecosystems and may inform conservation efforts and planning regarding the expected drivers of population demographics, distribution and connectivity.